2009
DOI: 10.2737/wo-gtr-82a
|View full text |Cite
|
Sign up to set email alerts
|

Forest Soil Disturbance Monitoring Protocol: Volume I: Rapid assessment

Abstract: The U.S. Department of Agriculture (USDA) prohibits discrimination in all its programs and activities on the basis of race, color, national origin, age, disability, and where applicable, sex, marital status, familial status, parental status, religion, sexual orientation, genetic information, political beliefs, reprisal, or because all or part of an individual's income is derived from any public assistance program. (Not all prohibited bases apply to all programs.) Persons with disabilities who require alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Williamson & Neilsen (2000) found that a single pass by a rubber-tired skidder increased soil bulk density by 22% in the upper 10 cm in Tasmania. Rutting can have detrimental impacts on site productivity by creating preferential flow patterns for overland water flow, decreasing infiltration and gaseous exchange (Page-Dumroese et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Williamson & Neilsen (2000) found that a single pass by a rubber-tired skidder increased soil bulk density by 22% in the upper 10 cm in Tasmania. Rutting can have detrimental impacts on site productivity by creating preferential flow patterns for overland water flow, decreasing infiltration and gaseous exchange (Page-Dumroese et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous classification systems for characterizing soil disturbance (e.g., Scott 2000;B.C. Ministry of Forests 2001;Heninger et al 2002;Page-Dumroese et al 2009). Regardless of the source of visual (qualitative) monitoring systems, they all include recognition that within a disturbance classification system, there are severity classes.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of lower forest layers, as a result of thinning, has been studied widely (Burova and Feklistov 2007;Feklistov and Torbik 2011;Levkovskaya and Sarnatsky 2013;Solgi et al 2015;Cambi et al 2015;Naghdi et al 2016;Dymov 2017). However, such studies mainly investigated the strip thinning carried out with heavy equipment, and several studies have focused on soil compaction and tracks as a result of forest management (Murphy et al 2004;Page-Dumroese et al 2009).…”
Section: Introductionmentioning
confidence: 99%